INEFFECTIVE REFUGEE STATUS DETERMINATION PROCESS: HINDRANCE TO DURABLE SOLUTION FOR REFUGEES RIGHTS AND PROTECTION - Nordin, Rohaida; Nor, Norilyani Hj Md; Rofiee, Rosmainie (Indonesia Law Review, 2021)
In any State of Asylum, the process of Refugee Status Determination (RSD) conducted by the United Nations High Commissioner for Refugees (UNHCR) is critical in facilitating asylumseekers to seek necessary protections. UNHCR ensures that asylum-seekers will not be returned involuntarily to the State of Origin where they could face persecution. As a long-term solution, UNHCR helps refugees to find appropriate and permanent solutions to their plights, either by repatriating them voluntarily to their homeland or assisting them to integrate into the States of Asylum or helping them to resettle in third States. In the absence of domestic legal protection in dealing with the refugees and asylum-seekers in Malaysia, a variety of operations are executed by UNHCR, including the admission, registration, documentation, and status determination of asylum seekers and refugees. To prevent the deportation of individuals qualified for international protection, UNHCR should reassess its RSD process in Malaysia, and consider alternative means that would be less burdensome and less risky for people who are fleeing violence and human rights violations. Primarily aimed at reassessing the RSD process in Malaysia using a doctrinal and comparative approach, the analysis is presented in four parts in this article. The first part provides for the definition and current statistics of refugee and asylum-seekers in Malaysia; the second part examines the mechanism of RSD conducted by UNHCR under international law; the third part focuses on how RSD operates in Malaysia; the last part reviews the mechanism of RSD in Indonesia and Brazil.